2016
DOI: 10.1189/jlb.1hi0216-062rr
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Tryptophan restriction arrests B cell development and enhances microbial diversity in WT and prematurely aging Ercc1−/Δ7 mice

Abstract: With aging, tryptophan metabolism is affected. Tryptophan has a crucial role in the induction of immune tolerance and the maintenance of gut microbiota. We, therefore, studied the effect of dietary tryptophan restriction in young wild-type (WT) mice (118-wk life span) and in DNA-repair deficient, premature-aged ( ) mice (20-wk life span). First, we found that the effect of aging on the distribution of B and T cells in bone marrow (BM) and in the periphery of 16-wk-old mice was comparable to that in 18-mo-old W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 62 publications
(68 reference statements)
2
25
1
1
Order By: Relevance
“…The reduction in Bacteroides and Clostridium coccoides in our study was very likely a specific effect of tryptophan deficiency, and not secondary to tryptophan-induced hypophagia, because caloric restriction has been to shown to increase Bacteroides in humans (39). In contrast to our data, a recent study reported that fecal concentrations of Bacteroidetes RC9 and Clostridiales were increased by 90% tryptophan restriction in mice (20). In that study, the diet composition was not detailed, and the diets of both control and tryptophan-restricted mice appeared to contain basal 10% casein.…”
Section: Obesitycontrasting
confidence: 95%
See 3 more Smart Citations
“…The reduction in Bacteroides and Clostridium coccoides in our study was very likely a specific effect of tryptophan deficiency, and not secondary to tryptophan-induced hypophagia, because caloric restriction has been to shown to increase Bacteroides in humans (39). In contrast to our data, a recent study reported that fecal concentrations of Bacteroidetes RC9 and Clostridiales were increased by 90% tryptophan restriction in mice (20). In that study, the diet composition was not detailed, and the diets of both control and tryptophan-restricted mice appeared to contain basal 10% casein.…”
Section: Obesitycontrasting
confidence: 95%
“…There is substantial evidence that tryptophan deficiency decreases food intake, feed efficiency, and growth rate in rodents and pigs (20,31). Consistent with these studies, we report that decreasing…”
Section: Figuresupporting
confidence: 90%
See 2 more Smart Citations
“…The featured paper ("Tryptophan restriction arrests B cell development and enhances microbial diversity in WT and prematurely aging Ercc12/D7 mice") by van Beek et al [5] reduces the complexity of CR interventions by feeding mice a diet only lacking Trp, as TR also delays aging of mice. This study breaks new ground by evaluating the consequences of TR for B cell development.…”
mentioning
confidence: 99%